Prostate-specific antigen levels in patients with risk factors for prostate carcinoma disorders - Mercedes Terreros; Yolanda Cristina Valdés; Lourdes Beatriz Gonzáles; Onay Adonys Mercader; Sebastián Romero (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Objective: To verify the association between the prostate-specific antigen (PSA) serum concentration and the presence of risk factors for prostate diseases in adult patients with urogenital infections. Materials and methods: Analytical cross-sectional study of PSA in 60 patients aged 40 to 65 years, from January to December 2013. PSA quantification was performed in serum by solid-phase chemiluminescence in two label cycles: 1. mouse monoclonal antibody (mAb); and 2. goat polyclonal antibody (pAbs). After each cycle the free antigen was removed. The readings were taken on the INMULITE ONE Siemens® automated equipment. From the PSA, 0.0-2.5 ng/ml was used to calculate the antigen distribution trend, and a bivariate statistical analysis of PSA was as opposed to previous exams, and endogenous and environmental risk factors detected. Results: Patients between 50-60 years of age, with a family history of urogenital and sexually transmitted infections, toxic habits, and exposure to occupational risk prevailed. Sixty-two percent of patients presented normal PSA levels, and the remaining presented slightly elevated and very high PSA levels. In the statistical analysis, a significant association (p < 0.001) of PSA was found as opposed to previous tests. A significant association (p = 0.001) was also found between PSA versus age, family history, personal pathological history, toxic habits, and risk exposure. Conclusion: The high association rate found between PSA versus age and other risk factors could be used as a predictive value for prostate cancer (Pca) or other prostate disorders.